USE OF ADVERTISING MATERIALS IN TEACHING A FOREIGN LANGUAGE - Ruslan M. Kliuchnyk; Olesia I. Opaleva (Alfred Nobel University Publisher, 2019)
The issues related to the use of advertising texts when teaching foreign languages have been considered in the article. In particular, the article considers their role in socio-cultural competence formation. The factors that make listening comprehension more difficult have been identified. Personal factors have been determined. The article stipulates that an advertising text comprises audio, video and text information. The connection between advertising discourse and the culture of people whose language is being studied has been considered in this article. The influence of political and economic globalization on advertisement has been analyzed. It has been proved that ethnic and cultural dimensions of advertisement are of crucial importance. Advertising texts appear to be quite similar owing to the influence of global market economy. The use of advertisement ensure that socio-cultural competence can be considered as an outcome of learning. The main purposes of video materials in foreign languages teaching have been considered. Positive attitude towards goods and services has been determined to be the main thing among other language advertising instruments. Sometimes advertisements can ruin negative or create positive stereotypes. The authors aim at analyzing the effectiveness of commercials using comparative tables. Thus, the students develop not only language skills but also improve their business and professional qualities. The scientists' views on the main aspects of using advertisements have been presented. Listening strategies suggested by Russian scientists have been analyzed. Comparative, systematic, structural-functional and axiological approaches have been used in the article. The examples of advertising texts, which could be used in teaching English, French and Polish, have been provided. Such texts can also explain the mechanisms of language functioning. Advertising materials of a French bank, of a British airline as well as a commercial of a Polish railroad company have been used. The article includes a set of tasks aimed at creating original advertising products. It has been proved that it is possible to create a complex of exercises involving advertisements, which could facilitate the perception of lexicon and grammar of the language learned. This can intensify the cognitive activity and stimulate creative use of the English language. The possibility has been considered to further use political advertising as a language learning tool.